On Psychological, Semantic and Structural Aspects of English Colour Terms - Avakyan, Naira; Nersissyan, Naira (Armenian Folia Anglistika, 2012)
Colour symbolism plays a great role in art, religious rituals and everyday life. Colour names can be encountered in phraseological units which are based on the semantic and psychological perceptions typical of a given nation and culture. They reflect the semantic, grammatical, lexicological and psychological peculiarities specific to a given language. The article discusses certain psychological, semantic and structural aspects of phraseological units with colour names.